Efficiency of Qatari banking industry: an empirical investigation - Abdul-Hamid, Abdul Wahab; Haron, Razali (Emerald Group Publishing Limited, 2017)
This paper examines the efficiency of the banking sector in Qatar. The paper utilizes 15 banks comprising Islamic, conventional and foreign banks for the duration of 2007 to 2011.Data Envelopment Analysis (DEA) technique is applied to compute technical efficiency, pure technical efficiency and scale efficiency. Also, Malmquist Productivity Index is used to identify the sources of productive efficiency of the banks. The results suggest that, Qatari banks are operating below optimum performance and thus there is still room for improvement. While conventional banks are the most efficient in Qatar in terms of technical and pure technical efficiencies, Islamic banks are most efficient in terms of scale efficiency. Besides, pure technical inefficiency dominated scale inefficiency in the Qatari banking sector. Moreover, as compared to the Islamic banks, conventional and foreign banks recorded a reduction in average technical efficiency during the duration of the 2008/2009 global financial crisis. In terms of productivity progress, all the Qatari banks were experiencing a decline in productivity mainly attributed to less technological innovation in the banking sector of Qatar. Most of the banks in Qatar do not have published data before 2007 and after 2011. There is less technological innovation in the banking sector of Qatar. Hence, bank managers in Qatar should focus on educating customers about modern banking technologies and other innovative banking services in Qatar. This study is a pioneering effort in the application of Data Envelopment Analysis and Malmquist Productivity Index to study about the banking sector in Qatar.